2014
DOI: 10.17569/tojqi.20328
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students' Experiences in Programming: Difficulties and Obstacles

Abstract: Programming courses become prominent as one of the courses in which undergraduate students are unsuccessful especially in departments which offer computer education. Students often state that these courses are quite difficult compared to other courses. Therefore, a qualitative phenomenological approach was used to reveal the reasons of the failures of the undergraduate students in programming courses and to examine the difficulties they confronted with programming. In this scope, the laboratory practices of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
(35 reference statements)
0
39
1
10
Order By: Relevance
“…The results indicated that there is no significant difference between their acceptance scores in terms of gender, programming background, and the high school type they graduated from and there is also no significant correlation between programming experience and their acceptance. These results mean that students have acceptance of Scratch regardless of gender and programming experience, although it was reported in the literature that the challenge of learning programming varies depending on gender (Howland & Good, 2015;Yurdugül & Aşkar, 2013) and experience (Lau & Yuen, 2011;Özmen & Altun, 2014). For this reason, the non-significancy has important implications for programming instruction at the university level, since this could be considered an advantage of Scratch for its widespread adoption by all learners, particularly novice programmers.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results indicated that there is no significant difference between their acceptance scores in terms of gender, programming background, and the high school type they graduated from and there is also no significant correlation between programming experience and their acceptance. These results mean that students have acceptance of Scratch regardless of gender and programming experience, although it was reported in the literature that the challenge of learning programming varies depending on gender (Howland & Good, 2015;Yurdugül & Aşkar, 2013) and experience (Lau & Yuen, 2011;Özmen & Altun, 2014). For this reason, the non-significancy has important implications for programming instruction at the university level, since this could be considered an advantage of Scratch for its widespread adoption by all learners, particularly novice programmers.…”
Section: Discussionmentioning
confidence: 82%
“…They believe that Scratch is useful for learning and teaching programming because it facilitates the algorithm creation process in an easier and more concrete manner. Creating algorithms for problems, lack of practice and knowledge are reported by Özmen and Altun (2014) as the major problems in learning programming. Additionally, the abstract nature of programming and lack of practical and concrete learning contexts are the reasons for difficulty, for especially novice learners (Lahtinen, Ala-mutka, & Järvinen, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used FCA for the programming course. The study results are rendered more important by the several studies [26,32,37,38] which concluded that the failure in programming stems from lack of time and practice because the students do not spend time on programming except when they are in the class. Thanks to this implementation, the students carried out the programming tasks outside the classroom and enriched their programming experiences via coding practices.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Some of the major problems identified for college students are abstract concepts, lack of understanding of the larger entities, lack of applications, and lack of practical and concrete learning situations [22]. A recently conducted study categorized the problems a novice learner faces as "programming knowledge (56%), programming skills (17%), understanding semantics (13%), and debugging (13%)" [29]. Regarding these problems, computer science educators and instructional technologists have been studying technological and pedagogical ways to make programming instruction easier and more effective.…”
Section: Introductionmentioning
confidence: 99%